Implementation of a protocol proposed by the Brazilian National Health Surveillance Agency for antibiotic use in very low birth weight infants - Maria Cristina F. Guedes Pinto; Arnaldo C. Bueno; Alan A. Vieira (Elsevier, 2013)
Objective: To analyze the implementation of a protocol proposed by the Brazilian National Health Surveillance Agency (Agência Nacional de Vigilância Sanitária - ANVISA) to improve sepsis diagnosis in very low birth weight newborns. Methods: This was a prospective study that evaluated the implementation of a protocol involving clinical and laboratory criteria (hematologic scoring system of Rodwell and C-reactive protein serial measurements), recommended by ANVISA, to improve the diagnosis of neonatal sepsis in very low birth weight newborns. The study included all patients who were born and remained in the neonatal intensive care unit until discharge or death, and excluded those with congenital diseases. The main outcomes measured in newborns before (2006-2007) and after implementation of the protocol (2008) were the rates of early and late-onset sepsis, use of antibiotics, and mortality. Means were compared by Student's t-test and categorical variables were compared by the chi-squared test; the significance level for all tests was set at 95%. Results: The study included 136 newborns with very low birth weight. There was no difference between groups regarding general clinical characteristics in the studied periods. There was, however, a decrease in the number of diagnoses of probable early-onset sepsis (p < 0.001), use of antimicrobial regimens (p < 0.001), and overall mortality and infection-related mortality (p = 0.009 and p = 0.049, respectively). Conclusion: The implementation of the protocol allowed improvement of sepsis diagnosis by reducing the diagnosis of probable early-onset sepsis, thus promoting efficient antimicrobial use in this population. Resumo: Objetivo: Analisar a aplicação de um protocolo proposto pela Agência Nacional de Vigilância Sanitária (ANVISA) para aprimorar o diagnóstico de sepse em recém-nascidos de muito baixo peso. Métodos: Estudo prospectivo que avaliou a aplicação de protocolo envolvendo critérios clínicos e laboratoriais (escore hematológico de Rodwell e dosagem seriada da proteína C-reativa), recomendado pela ANVISA, para aprimorar o diagnóstico de sepse neonatal em recém-nascidos de muito baixo peso. Participaram do estudo todos os pacientes que nasceram e permaneceram na Unidade Neonatal até a alta ou óbito, e foram excluídos aqueles com doenças congênitas. Os principais desfechos analisados entre os recém-nascidos antes da aplicação do protocolo (2006-2007) e após a aplicação do mesmo (2008) foram as taxas de sepses precoce e tardia, o uso de antimicrobianos e a mortalidade. As médias foram comparadas por meio de teste t e as variáveis categóricas pelo teste Qui-quadrado (X2); o nível de significância para todos eles foi fixado em 95%. Resultados: Foram incluídos no estudo 136 recém-nascidos de muito baixo peso. Não houve diferença entre os grupos em relação às características clínicas gerais nos períodos estudados. Houve, no entanto, redução na quantidade de diagnóstico de sepse precoce provável (p < 0,001), de uso de esquemas antimicrobianos (p < 0,001) e da mortalidade geral e associada à sepse (p = 0,009 e p = 0,049, respectivamente). Conclusão: A utilização do protocolo permitiu aprimorar o diagnóstico de sepse, reduzindo aquele de sepse precoce provável, promovendo, desta forma, o uso racional de antimicrobianos na população estudada. Keywords: Neonatal sepsis, Very low birth weight infant, Diagnosis, Palavras-chave: Sepse neonatal, Recém-nascido de muito baixo peso, Diagnóstico